Dhole pack size variation: Assessing the effect of Prey availability and Apex predator - Aishwarya Bhandari; Pallavi Ghaskadbi; Parag Nigam; Bilal Habib (Ecology and Evolution, 2021)
Abstract In multipredator systems, group sizes of social carnivores are shaped by the asymmetric intraguild interactions. Subordinate social carnivores experience low recruitment rates as an outcome of predation pressure. In South and Southeast Asia, the Tiger (Panthera tigris), Dhole (Cuon alpinus), and Leopard (Panthera pardus) form a widely distributed sympatric guild of large carnivores, wherein tigers are the apex predators followed by dhole and leopard. In this study, we attempted to understand the variation in pack size of a social carnivore, the dhole, at two neighboring sites in the Central Indian landscape. We further evaluated local‐scale patterns of variation in pack size at a larger scale by doing a distribution‐wide assessment across the dhole ranging countries. At the local scale, we found an inverse relationship between the density of tiger and pack size of dhole while accounting for variability in resources and habitat heterogeneity. Larger dhole packs (16.8 ± 3.1) were observed at the site where the tiger density was low (0.46/100 km2), whereas a smaller pack size (6.4 ± 1.3) was observed in the site with high tiger density (5.36/100 km2). Our results for the distribution‐wide assessment were concordant with local‐scale results, showing a negative association of pack size with the tiger densities (effect size −0.77) and a positive association with the prey abundance (effect size 0.64). The study advances our understanding to answer the age‐old question of “what drives the pack size of social predators in a multipredator system?” This study also highlights the importance of understanding demographic responses of subordinate predator for varying competitor densities, often helpful in making informed decisions for conservation and management strategies such as population recovery and translocation of species.